The Effectiveness of the Qawaid Wa Tarjamah Method to Improve Understanding of Basic Arabic Structures Mabni and Mu'rab - Hidayat, Surya; Munirul Abidin (Program Studi Pendidikan Bahasa Arab, 2024)
This research is motivated by the students' limited understanding of Arabic language concepts, particularly regarding mabni and mu'rab in Arabic grammar. This study aims to determine the effectiveness of the qawaid wa tarjamah method, in improving students' Arabic language skills, especially mabni and mu'rab in Qur'anic Junior High School Darul Fattah Boarding School. Using a descriptive quantitative approach, this study measured students' Arabic language skills before and after the application of the method. Data were gathered through multiple-choice tests and essay assessments, then analyzed using a paired sample t-test to compare the mean scores before and after the program. The results demonstrated a significant improvement in students after the application of the Qawaid Wa Tarjamah method. The findings of this study can serve as a foundation for developing more effective Arabic language learning programs in schools and contribute to enhancing the overall quality of Arabic language education.